BIM framework for the specification of information requirements in energy-related projects - Sanhudo, L (2021)
Purpose This paper aims to further the discussion on Building Information Modelling (BIM) legal requirements, providing a framework with key energy parameters capable of supporting the Appointing Party in the definition of the Exchange Information Requirements (EIR) for a BIM project appointment. The EIR is described in ISO-19650-1:2018 as a fundamental step in the information delivery cycle. Design/methodology/approach A literature review on the topic of BIM energy analysis was completed to identify current knowledge gaps and support the need for the proposed framework. Afterwards, the framework was established based on the review findings and the authors' domain knowledge. The applicability of the proposed framework was assessed through a case study, where several energy simulations were performed in three different design stages of the same BIM model. Findings This study identified a lack of standards and legislation capable of supporting the Appointing Party in the definition of energy-related BIM requirements. To this end, a new framework is proposed to mediate existing practices, linking prior knowledge with BIM's new reality. The study showcases the applicability of the framework, identifying that the performance of different energy studies involves distinct Level of Development (LOD) requirements, which in turn have an impact on the modelling time and cost. Originality/value A BIM framework for the specification of information requirements in energy-related projects was developed to support the Appointing Party. The framework presents appropriate parameters for energy analysis in each design stage, as well as the suitable LOD for the BIM model.